ANALISIS INVESTASI PENAMBAHAN AKTIVA TETAP (MESIN OVEN) PADA UD. WARNA SARI DI DESA SURANADI KECAMATAN NARMADA KABUPATEN LOMBOK BARAT - I GUSTI AGUNG DIDIT EKA PERMADI (GANEC SWARA, 2020)
The purpose of this study was to analyze the feasibility of an investment plan to add fixed assets (oven machines) by UD. Warna Sari in terms of financial aspects. This research is applied with data collection methods namely; case methods, data collection techniques: observation, interviews, and documentation. Data collection tools used in this study are questionnaire and tape recorder. Data analysis uses Net Present Value (NPV) analysis, Internal Rate of Return (IRR), Payback Period (PP), and Profitability Index (PI). From the results of this study can be concluded as follows: investment plans to add fixed assets (oven machines) are feasible to be implemented by UD. Warna Sari, when viewed from the financial aspect. This can be seen from the Payback Period (PP) = 0.09 years <1 year, Net Present Value (NPV) of Rp 473,330,270 is positive, IRR (105.04%)> RRR (50%), PI (60%) , 17)> 1 The investment decision to add fixed assets (oven machines) for business leader at UD. Warna Sari is feasible to be implemented to increase the production capacity of jackfruit dodol whose sales value continues to increase from year to year.